PHYSIOLOGICAL AND GENOTOXIC RESPONSES OF EARTHWORM Eudrilus eugeniae (Kingberg) EXPOSED TO SUBLETHAL LEVELS OF INDUSTRIAL EFFLUENT FROM ERODE DISTRICT, TAMIL NADU (INDIA) (Applied Biological Research, 2024)
The ecological risk is mostly assessed by evaluating the standard toxicological endpoints in earthworm toxicity assays, such as mortality and reproductive effects. The processes of toxic pollutants cannot comprehensively be understood by solely considering their endpoints. In this study, the usual testing by OECD, analysis of the composition of coelomic fluid, evaluation of micro- and binucleated cells, and histological studies were employed to assess the effects of industrial effluent on earthworm tissues. An additional endpoint in earthworm (Eudrilus eugeniae) was used to quantify the impact of industrial effluent on stress levels. The Comet assay was performed to evaluate the genotoxicity of industrial effluent. The effluent-treated earthworms exhibited a concentration- dependent increase in the number of micro- and binucleated cells, as compared to the control. It postulates that industrial pollution has an effect on cellular metabolism. Upon comparing the earthworms exposed to industrial effluent with those unexposed ones, a notable rise in DNA damage was observed. It confirmed the effectiveness of existing methods in monitoring the industrial pollution through biological means. It showed that evaluating DNA damage and levels of micro- and binucleated cells is a reliable approach. Histological studies revealed that longitudinal muscles, peritoneal epithelium, epidermis, and chloragogen cells of earthworm experienced substantial damage. The study concluded that industrial effluents pose a serious threat to earthworms, and more studies are needed to assess the acute and long-term toxicity of industrial effluent in contaminated areas and its actual influence on the environment.
Keywords: Coelomocytes; DNA damage; Comet assay; histopathology; industrial effluent